Performance and Pressure Drop Study on Shell and Tube and Double Pipe Heat Exchangers - Teodora Maria Fernandes Brito Da Silva (Equilibrium Journal of Chemical Engineering, 2026)
This study aims to analyze the performance and pressure drop of shell-and-tube and double-pipe heat exchangers. Tests were conducted using water as the hot and cold fluid. The flow rate variations used were 0.8 GPM, 1.0 GPM, and 1.2 GPM. The main parameters analyzed were the pressure drop values on the shell and tube sides for the shell-and-tube type and on the inner and outer pipes for the double-pipe type. The results showed that increasing the flow rate caused an increase in pressure drop in both types of heat exchangers. In the shell-and-tube type, the highest pressure drop was 0.017 psi at a flow rate of 1.2 GPM, while in the double-pipe type, it was 0.0101 psi at the same flow rate. These values are still far below the maximum allowable limit of 10 psi, so both devices are still feasible to operate. The relationship between the parameters (DG/μ)av and (ΔP)av shows an increasing trend with increasing fluid mass rate, indicating that viscosity and flow velocity affect pressure loss along the heat exchanger.